The Spiritual Transformation of the Samin Community in Tapelan Village: A Character Education Insight - Arif, Muhamad; Anwar, Chairul (Universitas Islam Negeri Raden Intan Lampung, 2023)
The Samin community, historically staunch followers of Iman Adam, resisted the injustices of the Dutch colonial rule using their spiritual beliefs. By the 1980s, a significant shift saw the Samin community in Tapelan Village converting from Iman Adam to Islam. This research probes the history of the Samin community's religious conversion in Tapelan Village from an educational standpoint, seeking insights that could augment national character education. Employing historical research methodologies, this study traverses through phases of (1) heuristic collection of historical sources, (2) validation through source criticism, (3) interpretative data analysis, and (4) historiography. The religious evolution of the Samin community can be demarcated into four pivotal phases: (1) reactive resistance against Dutch colonial policies, (2) a period of self-imposed isolation in teak forests, (3) a phase of skepticism and apathy extending to the initial days of independence, and (4) adaptive cooperation with the emergent environment post-1980s. Analyzed educationally, this conversion journey holds potential lessons for reinforcing national character education, emphasizing religious instruction, honesty, and unwavering loyalty to the nation. The Samin community's religious transformation in Tapelan Village not only chronicles their spiritual journey but also offers pedagogical perspectives instrumental in bolstering national character education.